2015
DOI: 10.1111/jnc.13233
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol prevents cadmium activation of Erk1/2 and JNK pathways from neuronal cell death via protein phosphatases 2A and 5

Abstract: Cadmium (Cd), a toxic environmental contaminant, induces neurodegenerative disorders. Resveratrol, a natural product, has been found to exert neuroprotective effects. However, little is known regarding the effect of resveratrol on Cd-evoked neurotoxicity. Here, we show that resveratrol effectively reversed Cd-elicited cell viability reduction, morphological change, nuclear fragmentation and condensation, as well as activation of caspase-3 in neuronal cells, implying neuroprotection against Cd-poisoning by resv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 75 publications
1
15
0
Order By: Relevance
“…Recent study also illustrated that resveratrol effectively suppressed the decline of hippocampal pCREB, a downstream target of BDNF, after developmental Pb exposure (Feng et al, 2016). In addition, resveratrol also exhibits potent antioxidant capacity due to its ability to remove free radicals and metals and to activate endogenous antioxidant enzymes (Liu et al, 2015; Whitehouse et al, 2016). In view of this, we examined how resveratrol modulate a number of the pro-oxidant and anti-oxidant biomarker (MDA, GSH, GSH-Px, CAT, and 8-OHdG) on Pb-induced oxidative stress process in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Recent study also illustrated that resveratrol effectively suppressed the decline of hippocampal pCREB, a downstream target of BDNF, after developmental Pb exposure (Feng et al, 2016). In addition, resveratrol also exhibits potent antioxidant capacity due to its ability to remove free radicals and metals and to activate endogenous antioxidant enzymes (Liu et al, 2015; Whitehouse et al, 2016). In view of this, we examined how resveratrol modulate a number of the pro-oxidant and anti-oxidant biomarker (MDA, GSH, GSH-Px, CAT, and 8-OHdG) on Pb-induced oxidative stress process in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Knowing that PPP5C has certain relevance with MAPK pathways via ERK1/2, JNK, and P38, 29 31 we detected ERK, JNK, and P38 levels after PPP5C downregulation and found that the phosphorylation of ERK1/2 and JNK was significantly increased with the non-phosphorylation was fixed ( Figures 6 and 7 ). But whether the phosphorylation or the non-phosphorylation level of the P38 molecule was immovable when the PPP5C changed.…”
Section: Discussionmentioning
confidence: 87%
“…CN IV: collagen type IV; de-PP2A: demethylated-PP2A; Erk1/2: extracellular signal-regulated kinase 1/2; GFP: green fluorescent protein; IGF-1: insulin-like growth factor-1; mTOR: mechanistic/mammalian target of rapamycin; PP2A: protein phosphatase 2A; PTEN: phosphatase and tensin homolog; shRNA: short hairpin RNA; S6K1: S6 kinase 1 Resveratrol can inhibit Erk1/2 at high concentrations (Roy, Chen, Fu, Shankar, & Srivastava, 2011). Recently, we have noticed that resveratrol activates PP2A activity (C. Liu et al, 2015). This led us to ask whether resveratrol inhibits IGF-1-induced cancer cell adhesion by targeting PP2A-Erk1/2 pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, PP2A, PTEN, and Akt function by regulating cell adhesion and migration (Haier & Nicolson, 2002;Kraus et al, 2002;Sontag & Sontag, 2006). In addition, studies have shown that resveratrol regulates PP2A, PTEN, and Akt (C. Liu et al, 2015;Y. Z. Liu et al, 2014).…”
mentioning
confidence: 99%